2010
DOI: 10.1016/j.sjpain.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perioperative S (+) ketamine infusion added to multimodal analgesia in patients undergoing ambulatory haemorrhoidectomy

Abstract: AbstractBackground and objectivePerioperative low-dose ketamine has been useful for postoperative analgesia. In this study we wanted to assess the analgesic effect and possible side-effects of perioperative low-dose S (+) ketamine when added to a regime of non-opioid multimodal pain prophylaxis. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 335 publications
(471 reference statements)
0
27
0
Order By: Relevance
“… 18 With the theoretical basis of preventing central sensitisation, S(+)-ketamine has been widely used as an adjuvant drug. 19 However, some key questions remained unanswered: What are the optimal dose, route of administration and drug compatibility recommended in clinical? How effective would S(+)-ketamine be when widely used in the Chinese population?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 With the theoretical basis of preventing central sensitisation, S(+)-ketamine has been widely used as an adjuvant drug. 19 However, some key questions remained unanswered: What are the optimal dose, route of administration and drug compatibility recommended in clinical? How effective would S(+)-ketamine be when widely used in the Chinese population?…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to the best of our knowledge, the SAFE-SK-A study is the first and largest-scale trial exploring the optimal approach for perioperative pain management in China to date. Previous evidence of S(+)-ketamine in the management of postoperative pain are only derived from several small scale randomised trials, as reported by Mendola et al (66 patients), 22 Spreng et al (77 patients) 19 and Ithnin et al (90 patients). 23 Here, we plan to recruit 12 000 patients and stratified according to the operation type, aiming to provide large-scale, randomised evidence for the analgesic effect and safety of S(+)-ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen new studies (n = 1,283 participants) [14][15][16][17][18][19][20][21][22][23][24][25][26][27] evaluated ketamine or (S)-ketamine (total, 27 studies; n = 2,757). Nine of 27 studies reported prevalence of any pain at 3 months, 16,20,22,26,29,37,[39][40][41] 16 studies at 6 months, [14][15][16][17]22,[24][25][26]30,[33][34][35][36][37]40,41 and five studies at 12 months. [14][15][16]28,30 Prevalence of any pain at 3 months ranged from 5.6 to 72.2% (mean, 35.0%) in the placebo arm and 5.6 to 83.3% (mean, 31.5%) in the ketamine arm.…”
Section: Ketaminementioning
confidence: 99%
“…All potentially relevant records were available as full‐text articles (n = 19). Of these, 12 were further excluded (not adequately controlled [n = 3], inadequate intervention [n = 3], no outcome of interest [n = 3], no general anaesthesia [n = 3]) . Seven reports comparing the administration of intraoperative ketamine with no intervention (no drug or placebo) were included .…”
Section: Resultsmentioning
confidence: 99%